2020
DOI: 10.1111/jwas.12744
|View full text |Cite
|
Sign up to set email alerts
|

Byssal re‐attachment behavior in the winged pearl oyster Pteria penguin in response to low salinity levels

Abstract: The effect of low salinity levels on byssal re‐attachment behavior in Pteria penguin juveniles was observed in the laboratory. Juvenile pearl oysters were submerged in seawater blended to 8.0, 12.0, 16.0, 20.0, 24.0, 28.0, and 32.0 salinity levels for a period of 48 hr. The sub‐lethal salinity level was greater than 20.0 psu. Although salinity levels of 20.0 and 24.0 psu did not affect the oyster survival, the observed byssogenesis activity was significantly reduced and locomotion activity was delayed. Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…A tolerance limit approaching 15‰ is consistent with the notion that T. crocea appears well adapted to hyposaline conditions (Neo et al, 2017) and aligns with the lowest medium-to long-term (i.e. days to weeks) salinity tolerable by most coral reef organisms (Coles & Jokiel, 1992), including other bivalves (Numagucki and Tanaka, 1986;Vasquez et al, 2020). There is also an indication that veligers experienced physiological stress as salinity approached this tolerance limit given the reduced survival and growth shown by larvae held at 20‰, when compared to those held at higher salinities.…”
Section: Introductionsupporting
confidence: 82%
“…A tolerance limit approaching 15‰ is consistent with the notion that T. crocea appears well adapted to hyposaline conditions (Neo et al, 2017) and aligns with the lowest medium-to long-term (i.e. days to weeks) salinity tolerable by most coral reef organisms (Coles & Jokiel, 1992), including other bivalves (Numagucki and Tanaka, 1986;Vasquez et al, 2020). There is also an indication that veligers experienced physiological stress as salinity approached this tolerance limit given the reduced survival and growth shown by larvae held at 20‰, when compared to those held at higher salinities.…”
Section: Introductionsupporting
confidence: 82%
“…Nevertheless, extreme fluctuations in salinity can defeat the defences and cause varying degrees of damage to marine molluscs, even may lead to heavy mortalities and economic losses (Carregosa, Figueira, et al, 2014; Gagnaire et al, 2006; Gajbhiye & Khandeparker, 2017). Among marine molluscs, previous studies are mostly concerned with the effects of salinity on behavioural response (Vasquez et al, 2021; Woodin et al, 2020), haemolymph chemistry and histopathological changes(Knowles et al, 2014), immune response (Casas et al, 2018; Gharbi et al, 2016; Zhang, Li, et al, 2020), gene expression(Gong et al, 2020; Nie et al, 2017) and molecular response (Li et al, 2021; Ni et al, 2021) in species such as Crassostrea gigas , C . nippona , C .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, extreme fluctuations in salinity can defeat the defences and cause varying degrees of damage to marine molluscs, even may lead to heavy mortalities and economic losses Gagnaire et al, 2006;Gajbhiye & Khandeparker, 2017). Among marine molluscs, previous studies are mostly concerned with the effects of salinity on behavioural response (Vasquez et al, 2021;Woodin et al, 2020), haemolymph chemistry and histopathological changes (Knowles et al, 2014), immune response (Casas et al, 2018;Gharbi et al, 2016;Zhang, Li, et al, 2020), gene expression (Gong et al, 2020;Nie et al, 2017) and molecular response (Li et al, 2021;Ni et al, 2021) in species such as Crassostrea gigas, C. nippona, C. virginica, Ruditapes philippinarum, R. decussatus, Cyclina sinensis, Sinonovacula constricta, Pteria penguin and Venerupis corrugate. Therefore, more knowledge is needed to understand the effects of acute salinity stress on the physiological and biochemical factors of other marine bivalve molluscs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that regulating ionic balance and osmotic pressure requires a large amount of energy in response to salinity stress (Li et al, 2014). In addition, there are many studies showing the effects of salinity stress on behavioral response, hemolymph chemistry and histopathological changes, and immune response of marine mollusks such as Ruditapes decussatus, Crassostrea gigas, C. virginica, Pteria penguin, and Venerupis corrugate (Knowles et al, 2014;Casas et al, 2018;Vasquez et al, 2020;Woodin et al, 2020;Zhang M. et al, 2020). However, the genes and pathways involved in salinity adaptation remain largely unknown, and more information is needed about the molecular effects of acute salinity stress on marine mollusks.…”
Section: Introductionmentioning
confidence: 99%